2010
DOI: 10.1111/j.1600-0447.2010.01571.x
|View full text |Cite
|
Sign up to set email alerts
|

Are multi family groups appropriate for patients with first episode psychosis? A 5‐year naturalistic follow‐up study

Abstract: Multi family groups appear to increase the chance of retaining patients in a follow-up study, but adjustment of the programme may be necessary with first episode psychosis patients to meet their needs better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…However, relapse prevention gains were not maintained at follow up. Closer inspection of the studies included in this follow-up meta-analysis revealed that only Chien et al (2016a) showed sustained gains in terms of risk of relapse at a 6 month follow, whereas Leavey et al (2004) and Rossberg et al (2010) with 9-month and 5-year follow ups respectively failed to show sustained gains. (Please see Table 3b in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…However, relapse prevention gains were not maintained at follow up. Closer inspection of the studies included in this follow-up meta-analysis revealed that only Chien et al (2016a) showed sustained gains in terms of risk of relapse at a 6 month follow, whereas Leavey et al (2004) and Rossberg et al (2010) with 9-month and 5-year follow ups respectively failed to show sustained gains. (Please see Table 3b in Supplementary Materials).…”
Section: Resultsmentioning
confidence: 91%
“…Seven studies were conducted in Europe, three in North America, two in Australia, one in Hong Kong and one in Mainland China. Eleven studies employed randomized controlled designs, one a controlled clinical trial (Browning et al, 2013) and two used an uncontrolled design (e.g., a cohort analytic design; Rossberg et al, 2010 and Rund et al, 1994). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only five empirical studies have examined the effect of family interventions in FEP. Two studies show that family work might be beneficial for patients with an FEP (Goldstein, Rodnick, Evans, May, & Steinberg, 1978;Zhang, Wang, Li, & Phillips, 1994), two studies show a worsened outcome for patients participating in family work interventions (Linszen et al, 1996;Rossberg et al, 2010), and one study shows no effect of the family intervention (Leavey et al, 2004).…”
mentioning
confidence: 98%
“…Third, it may be that the intervention is perceived as stressful and thereby interferes with the recovery process where stress reduction is the goal. Fourth, there might be a discrepancy between the patient's and the family members' needs (Rossberg et al, 2010).…”
mentioning
confidence: 99%